PEMAHAMAN KONSEP FUNGSI INVERS SISWA MELALUI PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Al Aini Aulia; I Nengah Parta; Santi Irawati (Jurnal Kajian Pembelajaran Matematika, 2017)
Abstract : Mathematics is a branch of science that play a pivotal role in human life . In the process of learning mathematics, many aspects must be considered so that the goal of learning can be achieved.  Learning paradigm that just makes students memorize many do not understand mathematical concepts. While understanding the concept is a very important factor in the learning of mathematics and basic things that should be owned by the students. Students who have a good understanding of the concepts that will have an impact on its ability to resolve problems and tasks given in the study of mathematics, this is indicated by the learning outcomes in the form of test scores. The success of achieving standards that have been defined. To achieve this, there are various strategies that can be used, one strategy is through cooperative learning of Jigsaw. Jigsaw type of cooperative learning characterized by spesialias assignment (team of experts). The study describes the students' understanding on the concept of inverse function through cooperative learning jigsaw. This research is a classroom action research using a qualitative approach, the instrument used (1) a test sheet, (2) observation sheets teacher activity and student activities, and (3) sheet autorefleksi. Based on the research, test data that 90, 63% of students to retrieve a value of more than or equal to 75 in accordance with the chief engineer, the data of teacher activity observation 98% category very well and observation data of student activity 90% very good category, as well as data auto reflection students feel happy with the model of learning is done. So meet the success criteria of the study.